POLITICAL BRANDING RIDWAN KAMIL PADA MASA KAMPANYE PILGUB JAWA BARAT 2018 MELALUI TWITTER - Sholihul Abidin; Ageng Rara Cindoswari (Prodi Ilmu Komunikasi Universitas Putera Batam, 2019)
Political branding is the use of a strategic way of consumer branding to build a political image. Ridwan Kamil won the election of governor of West Java in 2018. Different campaign strategies carried out by Ridwan Kamil were not only using the face to face communication model, but also direct communication. Social media has a role for Ridwan Kamil to communicate with his public during the campaign period to convey political messages. Ridwan Kamil's political branding during the campaign period of the 2018 elections in West Java's social media Twitter was formed through many aspects which included of appearance, personality and political messages. In addition to these aspects, other aspects that specifically shape political image through social media are the delivery of relations with constituents, the originality of leaders, responsiveness of technology, personal values ​​channeled, as well as key political messages. The key political message of Ridwan Kamil is done by providing development information, development plans, activity reports and conveying political values/ideologies. In addition, appearance as a candidate's identity also reflects the whole messages of political branding through the meaning of the costumes used. Ridwan Kamil indeed so far bears the celebrity social media political branding strategy carried out by Ridwan Kamil describing himself as a candidate figure who is open (minded?), close to the community, credible, and populist (egalitarian).Political Branding, Campaign, Twitter, election governor of West Java, Ridwan Kamil